THE EFFORTS OF JAVANESE LANGUAGE IN CREATING INTERNET TERMS - Ramadhan, Dimas; Puspitorini, Dwi (Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
This research aims to know how Javanese language faces the progressof times. The presence of social media as a new medium in communicating demands Javanese language to make adjustments. One form of adjustment of Javanese language can be seen through the interface display of Javanese-language Facebook that fullof internet terms. This research examines how Javanese language creates and matches the Internet terms contained in the interface display of Javanese-language Facebook. This research uses a qualitative method that describes the findings obtained from the glossary of Javanese-language Facebook. The results of this research indicate that the term-matching on the interface display of Javanese-languageFacebook is mostly done by loan, not by translation or creating the term of internet in Javanese language. It proves that Javanese language is open and flexible to foreign influences. This is the characteristic that causes Javanese language to live and survive for centuries until now. Keywords: Javanese language, loan, progress, internet